2023
DOI: 10.1038/s41380-023-01971-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural inequities contribute to racial/ethnic differences in neurophysiological tone, but not threat reactivity, after trauma exposure

Abstract: Considerable racial/ethnic disparities persist in exposure to life stressors and socioeconomic resources that can directly affect threat neurocircuitry, particularly the amygdala, that partially mediates susceptibility to adverse posttraumatic outcomes. Limited work to date, however, has investigated potential racial/ethnic variability in amygdala reactivity or connectivity that may in turn be related to outcomes such as post-traumatic stress disorder (PTSD). Participants from the AURORA study (n = 283), a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…However, trauma exposure may have been associated with potentiated amygdala reactivity and obscured outcomes associated with neighborhood disadvantage. AURORA analyses in 2023 did not observe between-group differences in reactivity during the fearful faces task among survivors of recent trauma when stratified by prior sexual trauma or by ethnoracial group with differing levels of neighborhood disadvantage . However, differences in amygdala intrinsic connectivity by ethnoracial group were mediated by differential exposure to neighborhood disadvantage .…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…However, trauma exposure may have been associated with potentiated amygdala reactivity and obscured outcomes associated with neighborhood disadvantage. AURORA analyses in 2023 did not observe between-group differences in reactivity during the fearful faces task among survivors of recent trauma when stratified by prior sexual trauma or by ethnoracial group with differing levels of neighborhood disadvantage . However, differences in amygdala intrinsic connectivity by ethnoracial group were mediated by differential exposure to neighborhood disadvantage .…”
Section: Discussionmentioning
confidence: 52%
“…This study is reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline. The included neuroimaging data have been previously reported, but these analyses are unique …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These covariates were selected owing to their potential confounding role with either the exposure or the outcome. For example, prior studies have shown that less favorable neighborhood conditions disproportionately impact minoritized racial and ethnic groups (3), and research has also demonstrated that racial discrimination relates to amygdala activity and FC (15,16) and these neural patterns vary by racial and ethnic group (20). Study participants completed the Beck Depression Inventory (BDI-II) (32) and the Beck Anxiety Inventory (BAI) (33) for subjective measures of depressive and anxiety symptoms, respectively.…”
Section: Covariatesmentioning
confidence: 99%